Formulación de estrategias para minimizar conflictos gente-fauna en la parroquia Buenavista - Buele Erazo, Iván Andrey (2024)
Nowadays, the problem of people-fauna conflict is quite serious at a global level and is continually being magnified by human activities and the advance of climate change. In Ecuador, little research has been carried out on this issue, even though these conflicts are common throughout the country, especially in rural areas, where the control authorities carry out few actions to avoid these conflicts. This research was carried out in the Buenavista parish, Chaguarpamba canton, Loja province, which has a problem of deforestation and invasive agricultural activities. In these circumstances, through surveys we interacted with the inhabitants of the parish to find out the species of problematic fauna, the severity and frequency of conflicts and what actions they have taken to avoid or reduce this situation; based on this, some strategies were adopted for the conditions of the parish, including the use of physical barriers, visual and chemical deterrents to reduce the severity and frequency of people-fauna conflicts, which were socialized with the inhabitants interested in resolving this problem. During this research, it became evident that there is a low level of environmental education in the parish, which means that the inhabitants are not aware of environmental legislation and do not know what protocols should be followed to report an environmental crime. It is therefore essential to make efforts to provide the inhabitants with information that will enable them to solve their environmental problems and thus prevent this situation from continuing over time.